2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35158
|View full text |Cite
|
Sign up to set email alerts
|

Results of Integrating a Maker Space into a First-Year Engineering Course

Abstract: Engineering and Applied Science Education department. She previously specialized in service learning while teaching at the Arizona State University in the Engineering Projects in Community Service (EPICS) program. Her current teaching and research interests are in developing study skills and identity in first-year engineering students and improving retention rates. She acts as the faculty liaison for the University of New Haven Makerspace and facilitates student and faculty training. She received her Ph.D. in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…confidence, motivation) were seen to be higher in students that voluntarily used the universities' makerspace than in students that did not [24]. When this information is coupled with another study showing that early involvement with makerspaces in a classroom setting led to a greater likelihood of students using the makerspace outside of class [18], it indicates that the incorporation of makerspaces early on in engineering curricula may bring a number of quantitative and qualitative benefits to students' learning experiences.…”
Section: Makerspaces In Engineering Educationmentioning
confidence: 82%
See 3 more Smart Citations
“…confidence, motivation) were seen to be higher in students that voluntarily used the universities' makerspace than in students that did not [24]. When this information is coupled with another study showing that early involvement with makerspaces in a classroom setting led to a greater likelihood of students using the makerspace outside of class [18], it indicates that the incorporation of makerspaces early on in engineering curricula may bring a number of quantitative and qualitative benefits to students' learning experiences.…”
Section: Makerspaces In Engineering Educationmentioning
confidence: 82%
“…In an analysis of training for technical procedures in the medical field, Clanton et al [17] have proposed that the incorporation of practica contributes to a positive feedback loop of content engagement: hands-on training increases student confidence, which increases their likelihood/willingness to use these skills, providing further practice, and further increasing confidence. Similar dynamics may hold in engineering, as a study by Gillespie and Nossoni [18] indicated that introducing students to fabrication methods and resources in a college "makerspace" increased their likelihood of visiting the makerspace for extracurricular reasons. These practical experiences of specific technical processes can thus be seen to provide potential mastery experiences that strongly contribute to the development of self-efficacy.…”
Section: Active Learning Styles -Experiential and Project-based Learningmentioning
confidence: 84%
See 2 more Smart Citations